The Performance of the 3DES and Fernet Encryption in Securing Data Files - Siti Munirah Mohd; Shafinah Kamarudin; Norhanizah Yahya; Sazlinah Hasan; Muhammad Luqman Mahamad Zakaria; Sahimel Azwal Sulaiman; Djoko Budiyanto Setyohadi (Little Lion Scientific, 2024)
Indexed by Scopus